Perbandingan Teori Komunikasi Islam dan Barat; Menurut Pemikiran Al-Farabi Telaah Epistimologi dan Ontologi di Era Digital: Penelitian - Rismayanti; Mailin; Rubino (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study examines a comparison of communication theories from Islamic and Western perspectives, with an emphasis on Al-Farabi's thought, particularly in the context of epistemology and ontology in the digital era. Amidst rapid advances in information technology, communication has become a crucial aspect of social and cultural interaction, necessitating an understanding of how each tradition views the communication process. Western communication theory, often rooted in positivist and empirical approaches, emphasizes the technical and functional aspects of communication. In contrast, communication theory in Islam, influenced by spiritual and moral values, emphasizes the importance of intention, ethics, and social context in the communication process. Al-Farabi, as one of the great philosophers who integrated Greek thought with Islamic teachings, made significant contributions to understanding communication as a process that not only involves the exchange of information but also the formation of identity and community. This study uses qualitative analysis methods to explore Al-Farabi's works, including "Al-Madina al-Fadila" and "Risalah Fi al-'Aql," to unearth the epistemological and ontological concepts underlying his communication theory. This research finds that Al-Farabi viewed communication as a bridge connecting the individual with society and God, functioning to achieve happiness and the common good. In the context of the digital era, where information can be spread quickly and widely, Al Farabi's thought offers a relevant perspective for understanding new challenges in communication, such as the spread of fake news and the crisis of trust. The results of this study indicate that although there are fundamental differences between Islamic and Western communication theories, there is potential for them to complement and enrich our understanding of communication in modern society. Thus, this research contributes to the academic discourse on cross cultural communication and provides recommendations for the application of more ethical and sustainable communication values in the digital era. The final results are expected to serve as a reference for academics, practitioners, and policymakers in formulating more effective and value-based communication strategies.